Surgical Management of Mandibular Odontogenic Myxoma Utilizing CAD/CAM Technology: A Case Report - Helinko Orvokki; Irace Alexandria L; Suomalainen Anni; Hagström Jaana; Mesimäki Karri (Meddocs Publishers, 2022)
Background: Odontogenic myxoma (OM) is a benign intraosseous tumour of the jaw usually treated by surgery. Computer-aided design and manufacturing (CAD/CAM) technology may optimize preoperative planning of the resection and jaw reconstruction.
Case Report: A 29-year-old female was diagnosed with mandibular odontogenic myxoma. A large, benign but potentially infiltrating, and locally aggressive tumour required radical surgical treatment. CAD/CAM technology facilitated preoperative planning for block resection and immediate reconstruction of the mandible. CAD/CAM was utilized to determine the resection margins planned according to cone beam computed tomography (CBCT) data and manufacture the reconstruction plate and cutting guides.
Clinical implications: CAD/CAM can be utilized to produce 3D models of OM, cutting guides, and patient-specific implants, making it a valuable tool in the management of this disease. Future investigations should study how operative times and clinical outcomes are affected by this technology.